2017
DOI: 10.1002/ijc.31018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic conditions and breast cancer risk among Los Angeles County Filipina Americans compared with Chinese and Japanese Americans

Abstract: Accumulating evidence suggests that the aggregation of common metabolic conditions (high blood pressure, diabetes and dyslipidemia) is a risk factor for breast cancer. Breast cancer incidence has risen steadily in Asian American women, and whether these metabolic conditions contribute to breast cancer risk in certain Asian American subgroups is unknown. We investigated the role of physician-diagnosed hypertension, high cholesterol and diabetes separately, and in combination, in relation to the risk of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…[ 4 9 ] Meanwhile, studies on MetS, another potential risk factor with an increasing prevalence worldwide, produced inconsistent results, especially in Asians. [ 24 28 ] In the present study, we found a much higher NLR in pre/perimenopausal women, compared with postmenopausal women (1.93 ± 0.85 vs 1.72 ± 0.76, P < .001). Similar conclusion was drawn in a study of Chen et al that women <50 years old had significantly higher NLR than women of 51 to 70 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…[ 4 9 ] Meanwhile, studies on MetS, another potential risk factor with an increasing prevalence worldwide, produced inconsistent results, especially in Asians. [ 24 28 ] In the present study, we found a much higher NLR in pre/perimenopausal women, compared with postmenopausal women (1.93 ± 0.85 vs 1.72 ± 0.76, P < .001). Similar conclusion was drawn in a study of Chen et al that women <50 years old had significantly higher NLR than women of 51 to 70 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…Currently, lower prevalence of the most harmful cancer risk factors, and perhaps the 'healthy migrant effect' (migrant populations often being in better health than the indigenous population in their new home country), largely outweighs the harmful effect of deprivation to provide a 'cancer protective' effect of non-White minority ethnicity [4,58,59]. But there is evidence that as minority ethnic groups become more established in their adopted home nations, their risk factor prevalence and corresponding cancer incidence rates become increasingly similar to those of the indigenous population [60][61][62]. This coupled with overall higher rates of deprivation in non-White minority ethnic groups could in future mean the association between deprivation and cancer incidence is actually compounded in these groups.…”
Section: Comparison With Existing Evidencementioning
confidence: 99%
“…Thus, our findings both extend and are in part supported by others. A stronger association of BMI, weight gain and WHR with breast cancer risk was observed in postmenopausal Asian and Asian-American women than in non-Hispanic white women [24], and a dose-response association was found between unfavorable metabolic factors (high BP, diabetes and dyslipidemia) and breast cancer risk among Asian-Americans born or residing in the USA for >20 years [25]. Ethnic disparities in BMI and risk for other chronic diseases have been observed [26], and, based on the same population as in the present study, a high prevalence of obesity-dependent type 2 diabetes was found among women from Pakistan and Sri Lanka [6].…”
Section: Discussionmentioning
confidence: 89%